Specifics of the autonomous energy power unit dynamic processes’ modeling - et. al., A. A. Verlan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Significant features of modern autonomous power units, along with increasing complexity of structures and modes and increasing requirements for quality of operation, are the heterogeneity of their composition, the presence of links with distributed parameters, changing parameters during operation, the presence of computer components control, monitoring and diagnostics. A characteristic feature of controlled autonomous power units is the diversity of elements that are part of them. This, in turn, usually creates inhomogeneity in the mathematical description of the system. Physical heterogeneity is caused by the presence of elements that are different in physical essence (mechanical, electrical, optical, magnetic and electromagnetic, etc.). Functional heterogeneity is manifested in the presence of different purpose signals (control, measuring, duplicating, auxiliary, etc.). Thus, modern autonomous power units belong to the class of complex inhomogeneous dynamic systems.These features cause the emergence of new requirements for methods and tools for mathematical modeling of dynamic processes in autonomous power units, in particular the need to move from common in practice autonomous study of individual components, to a comprehensive study of the system as a whole using macromodels, model building according to experimental data, increasing the adequacy of mathematical models by rationally taking into account the distribution of parameters of the relevant links, the possibility of rapid changes in the composition of computer models, taking into account physical and functional heterogeneity.The article considers the methods of construction of mathematical models of dynamic processes in modern autonomous power units and in their control systems, diagnostics and testing on the basis of expansion of forms of mathematical descriptions with involvement of integral operators and Volterra equations.